Labour migration to the UK from Eastern partnership countries - Kenneth Clark; Stephen J. Drinkwater (IZA Journal of European Labor Studies, 2014)
Stocks and flows of migrant workers from EaP countries in the UK are relatively small, and flows have declined recently following changes to UK immigration policy and the onset of recession. The demographic profile of migrants from EaP countries is similar to that of EUA8 migrants but employment rates have been much lower. A large proportion of migrants to the UK from EaP countries are highly educated but this has not led to such high levels of occupational attainment as groups such as EU14 migrants. Despite the potential for increased migration to fill skill gaps, immigration policies and attitudes to immigrants are likely to restrict future flows.
Keywords: J61; F22; 330; Migration; Eastern partnership countries; United Kingdom; Labour market